Role of topoisomerase II α and Ki -67 biomarkers in pituitary tumors - Chhanda Das; Madhumita Mukhopadhyay; Satinath Mukhopadhyay; Avijit Hazra (Journal of Pathology of Nepal)
Background: Pituitary Adenoma, a neoplastic proliferation of anterior pituitary hormone producing cells, is mainly considered benign but some are clinically aggressive and recurrent and very rarely malignant. From recent advances in pathological and molecular study, there is a continuous search for numerous prognostic biomarkers, to analyze better tumor behavior and prediction of response to treatment and recurrences. This study was conducted to see the epidemiological spectrum of pituitary tumors and to evaluate the correlation of TOPOISOMERASE IIα (Topo 2A), and Ki-67 biomarker with recurrence, aggressiveness, hormone subtype, radiological invasiveness, and prognostic grade of pituitary tumors.